Delivery Systems for Plasma-reactive Species and their Applications in the Field of Biomedicine - Biazar, Esmaeil; Aavani, Farzaneh; Zeinali, Reza; Kheilnezhad, Bahareh; Taheri, Kiana; Yahyaei, Zahra (Current Drug Delivery, 2024)
Cold atmospheric plasma (CAP) is an ionized matter with potential applications in various medical fields, ranging from wound healing and disinfection to cancer treatment. CAP's clinical usefulness stems from its ability to act as an adjustable source of reactive oxygen and nitrogen species (RONS), which are known to function as pleiotropic signaling agents within cells. Plasma-activated species, such as RONS, have the potential to be consistently and precisely released by carriers, enabling their utilization in a wide array of biomedical applications. Furthermore, understanding the behavior of CAP in different environments, including water, salt solutions, culture medium, hydrogels, and nanoparticles, may lead to new opportunities for maximizing its therapeutic potential. This review article sought to provide a comprehensive and critical analysis of current biomaterial approaches for the targeted delivery of plasma-activated species in the hope to boost therapeutic response and clinical applicability.
Keywords: delivery